2022
DOI: 10.32582/aa.63.2.1
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of environmental risk related to the polycyclic aromatic hydrocarbons (PAH) in the sediments along the eastern Adriatic coast

Abstract: Polycyclic aromatic hydrocarbons (PAH) were investigated in the sediments at 24 locations in the coastal area of Adriatic Sea. Total PAH concentrations ranged from 14,98 to 26145,62 µg kg-1, with the highest levels determined in the sediments of Šibenik Bay and the lowest in the sediment near Island of Pag. Unsubstituted PAH were prevailing PAH group in the sediments from the Šibenik Bay and in the Coastal area, while methyl-substituted PAH were dominant group in the sediments of the Kaštela Bay. In order to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 15 publications
(33 reference statements)
0
0
0
Order By: Relevance
“…When all 16 PAH compounds were considered, TEQ values at most stations exceeded 600 µg kg −1 , indicating a high carcinogenic risk associated with sediment PAH concentration in Šibenik Bay. Results obtained by calculation of TEQ are in good agreement with the results of PAH-related sediment toxicity obtained by applying the sediment quality guidelines, where a high environmental risk was observed for the total area of Šibenik Bay [38]. However, in the same study, the results of the bioassay application indicated poor environmental status associated with the PAH sediment concentration at stations outside Šibenik Bay.…”
Section: Benzo[a]pyrene Equivalent Toxicity Of Pah Mixtures In the Ad...supporting
confidence: 85%
See 1 more Smart Citation
“…When all 16 PAH compounds were considered, TEQ values at most stations exceeded 600 µg kg −1 , indicating a high carcinogenic risk associated with sediment PAH concentration in Šibenik Bay. Results obtained by calculation of TEQ are in good agreement with the results of PAH-related sediment toxicity obtained by applying the sediment quality guidelines, where a high environmental risk was observed for the total area of Šibenik Bay [38]. However, in the same study, the results of the bioassay application indicated poor environmental status associated with the PAH sediment concentration at stations outside Šibenik Bay.…”
Section: Benzo[a]pyrene Equivalent Toxicity Of Pah Mixtures In the Ad...supporting
confidence: 85%
“…However, in the same study, the results of the bioassay application indicated poor environmental status associated with the PAH sediment concentration at stations outside Šibenik Bay. This suggests that assessing the toxicity of PAH solely on sediment concentration may significantly underestimate the environmental risk [38].…”
Section: Benzo[a]pyrene Equivalent Toxicity Of Pah Mixtures In the Ad...mentioning
confidence: 99%
“…During the industrial operation, various types of coal were used, namely, lignite, anthracite, and brown coal, originating from mining sites with increased natural radioactivity [31]. Since the site was not subjected to any treatment for more than a decade, spontaneous revegetation occurred, currently consisting of different species of Mediterranean terrestrial flora, providing a research opportunity to conduct studies and assessments in specific environmental conditions [32,[34][35][36][37]. A previous study by Skoko et al [33] focused on the radioactivity of the soil in Kaštela Bay and provided data on background activity concentrations based on samples from a control site which was not affected by previous industrial activities.…”
Section: Assessment Sitementioning
confidence: 99%
“…Previous radiological studies conducted at the location include research of the chemical and radiological profile of the coal ash landfill [31], studies focused on research aspects of plant uptake of radionuclides from coal ash and slag [32], investigations of the radioactivity of the Mediterranean flora [33], a risk assessment of the legacy disposal site [34], research on natural and anthropogenic radionuclides in the karstic coastal part of the location [35,36], and an assessment of the environmental risk related to polycyclic aromatic hydrocarbons [37].…”
Section: Introductionmentioning
confidence: 99%